The evolution of motor cortical dysfunction in amyotrophic lateral sclerosis. Issue 6 (June 2017) - Shibuya, Kazumoto; Simon, Neil G.; Geevasinga, Nimeshan; Menon, Parvathi; Howells, James; Park, Susanna B.; Huynh, William; Noto, Yu-ichi; Vucic, Steve; Kiernan, Matthew C.
Highlights: Alterations of cortical function in amyotrophic lateral sclerosis have been investigated. Cross-sectional and longitudinal analyses revealed a gradual reduction in intracortical inhibition. These findings suggest dysfunction of inhibitory interneurons with disease progression. Abstract: Objective: The present study aimed to investigate alterations in cortical function in amyotrophic lateral sclerosis (ALS) related to disease progression. Methods: In total, clinical assessments were evaluated in 189 ALS patients, combined with assessment of cortical function utilising threshold tracking transcranial magnetic stimulation. Results were compared with disease stage. Disease stage was defined in three ways: (1) as a proportion of disease duration in deceased patients; (2) from the time of ALS onset; and (3) using the ALS rating scale-revised (ALSFRS-R). Results: Prospective studies in ALS patients demonstrated decreased neurophysiological index ( p < 0.0001) and decreased compound muscle action potential (CMAP) ( p < 0.0001), combined with abnormalities of central function including prolonged central motor conduction time (CMCT) ( p < 0.05), increased motor evoked potential/CMAP amplitude ratio ( p < 0.0001) and decreased short interval intracortical inhibition (SICI) ( p < 0.001). SICI at 3 ms ( p < 0.05, β = −0.21) and averaged SICI ( p < 0.05, β = −0.21) decreased with disease progression, measured using proportion of disease duration. Alternatively, using time from disease onset, CMCT prolonged with disease progression ( p < 0.01, β = 0.25), while ALSFRS-R decline correlated with decreased SICI at 3 ms ( p < 0.01, β = 0.20). Conclusions: Clinical measures combined with assessment of cortical function established that SICI decreased with disease progression. Significance: These findings may suggest dysfunction of inhibitory interneurons with disease progression.